Candidate Effectors of Plasmodiophora brassicae Pathotype 5X During Infection of Two Brassica napus Genotypes - Galindo-González, Leonardo; Hwang, Sheau-Fang; Strelkov, Stephen E. (Frontiers in Microbiology, 2021)
Clubroot, caused by Plasmodiophora brassicae, is one of the most important diseases of canola (Brassica napus) in Canada. Disease management relies heavily on planting clubroot resistant (CR) cultivars, but in recent years, new resistance-breaking pathotypes of P. brassicae have emerged. Current efforts against the disease are concentrated in developing host resistance using traditional genetic breeding, omics and molecular biology. However, because of its obligate biotrophic nature, limited resources have been dedicated to investigating molecular mechanisms of pathogenic infection. We previously performed a transcriptomic study with the cultivar resistance-breaking pathotype 5X on two B. napus hosts presenting contrasting resistance/susceptibility, where we evaluated the mechanisms of host response. Since cultivar-pathotype interactions are very specific, and pathotype 5X is one of the most relevant resistance-breaking pathotypes in Canada, in this study, we analyze the expression of genes encoding putative secreted proteins from this pathotype, predicted using a bioinformatics pipeline, protein modeling and orthologous comparisons with effectors from other pathosystems. While host responses were found to differ markedly in our previous study, many common effectors are found in the pathogen while infecting both hosts, and the gene response among biological pathogen replicates seems more consistent in the effectors associated with the susceptible interaction, especially at 21 days after inoculation. The predicted effectors indicate the predominance of proteins with interacting domains (e.g., ankyrin), and genes bearing kinase and NUDIX domains, but also proteins with protective action against reactive oxygen species from the host. Many of these genes confirm previous predictions from other clubroot studies. A benzoic acid/SA methyltransferase (BSMT), which methylates SA to render it inactive, showed high levels of expression in the interactions with both hosts. Interestingly, our data indicate that E3 ubiquitin proteasome elements are also potentially involved in pathogenesis. Finally, a gene with similarity to indole-3-acetaldehyde dehydrogenase is a promising candidate effector because of its involvement in indole acetic acid synthesis, since auxin is one of the major players in clubroot development.